The effect of shared temporal cognitions and Pacing styles on intragroup conflict in portuguese healthcare teams - Queimado, Alexandra Coelho de Meireles de Oliveira (2016)
This study aimed to evaluate the impact of two specific dimensions of time-related matters (shared temporal cognitions and pacing styles), as a cognitive contextual factor, on different types of team conflict. We hypothesized that the relationship between shared temporal cognitions and the different types of conflict is moderated by pacing styles. A total of 30 teams (245 individuals) participated in this study. All teams were part of different Portuguese healthcare centers. Globally, the results didn’t support the hypotheses concerning the direct influence of time-related matters on intragroup conflicts, although shared temporal cognitions were related to all types of intragroup conflict. The results didn’t support the hypothesis of the moderating role of pacing styles on the relationship between shared temporal cognitions and task conflict, relationship conflict and temporal conflict. Therefore, shared temporal cognitions help teams to avoid getting involved in conflicts that may affect their work while being deadline-action oriented doesn’t mean that tension will build up in the team. KEY-WORDS: